2022
DOI: 10.3389/fonc.2022.802548
|View full text |Cite
|
Sign up to set email alerts
|

Early-Stage Loss of GALNT6 Predicts Poor Clinical Outcome in Colorectal Cancer

Abstract: Colorectal adenocarcinomas arise from luminal lining epithelium of the colorectal tract which is covered with highly glycosylated mucins. Mucin O-glycosylation is initiated by a family of polypeptide N-acteylgalactosaminyltransferases (GALNTs). This study examined GALNT6 protein expression in 679 colorectal tumors, including 574 early-stage and 105 late-stage cancers. GALNT6 expression in cancer tissue varied widely between patients ranging from high levels to complete loss. Loss of GALNT6 occurred in 9.9% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The expression profile analysis revealed that, GALNT6 was highly expressed in 15 tumors among the 20 tumors with differential GALNT6 expression. According to the literature search results, higher GALNT6 expression has been found in breast carcinoma, 11 ovarian carcinoma, 13 lung adenocarcinoma, 35 and colon adenocarcinoma, 36 which is consistent with our study. Our study is the first to demonstrate that high GALNT6 expression occurs in BLCA, CHOL, HNSC, LUSC, PCPG, READ, UCEC, UCS, LAML, TGCT and THYM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The expression profile analysis revealed that, GALNT6 was highly expressed in 15 tumors among the 20 tumors with differential GALNT6 expression. According to the literature search results, higher GALNT6 expression has been found in breast carcinoma, 11 ovarian carcinoma, 13 lung adenocarcinoma, 35 and colon adenocarcinoma, 36 which is consistent with our study. Our study is the first to demonstrate that high GALNT6 expression occurs in BLCA, CHOL, HNSC, LUSC, PCPG, READ, UCEC, UCS, LAML, TGCT and THYM.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that GALNT6 level is related with survival in patients with early-stage colorectal cancer, breast cancer, and ovarian cancer. 11 , 13 , 36 A high GALNT6 level is an important risk factor for predicting poor OS and PFS; 11 , 13 however, early-stage colorectal cancer patients with GALNT6 protein loss have been found to have significantly shorter OS than those with positive GALNT6 expression. 36 In this study, we have revealed the prognostic significance of GALNT6 in multiple cancer types, including bladder cancer, brain cancer, eye cancer, cervical squamous cell carcinoma and endocervical, esophageal carcinoma, liver hepatocellular carcinoma, pheochromocytoma and paraganglioma, and uterine corpus endometrial carcinoma, which has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioblastoma (GB) is the most common malignant primary brain tumor in adults, with a survival period of post-standard treatment averaging 14.6 months [ 35 , 36 ]. Recurrence within 6–9 months after initial therapy is common, motivating exploration of multikinase inhibitors like Regorafenib (REGO) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high expression level of GALNT6 was signi cantly associated with the low expression levels of E-cadherin and β-catenin and the high expression levels of MMP9, these ndings indicated that GALNT6 could provide a insight into the characterization of gastric cancer (GC) as well as contribute to the development of an e cient prognostic indicator for GC [39]. Additionally, studies have shown that loss of GALNT6 enzyme in early-stage colorectal cancer predicts poor clinical outcomes in colorectal cancer [40]. In lung cancer, GALNT6 promotes the invasion and metastasis of by enhancing the MEK1/2/ERK1/2 pathway through the glycosylated chaperone protein GRP78 [19].…”
Section: Galnt6 and Immune Microenvironment Dynamic In Bladder Cancermentioning
confidence: 97%